Emberyonal Rhabdomyosarcoma of The Prostate In Young Sudanese Male: Case Report - Hassan, Amer Abbo; Amer Abbo, H Basil; Osman, Hatim (Indian Journal of Case Reports, 2026)
Rhabdomyosarcoma (RMS) is an aggressive soft-tissue cancer. Embryonal RMS (ERMS) is common in whenoriginating in the prostate, usually carrying a poor prognosis. A 15-year-old male from Sudan presented with acuteurinary retention. Examination and biopsy confirmed ERMS of the prostate with metastasis to the lungs and pelviclymph nodes. Despite palliative surgery, transurethral resection of the prostate, and chemotherapy, the patient passedaway 6 months later due to chemotherapy complications. This is the first documented case of prostatic ERMS inSudan. The case underscores the malignancy’s aggressive nature and the critical need for early detection, accurate diagnosis, and multidisciplinary care to improve survival rates.